Laporan Kasus: Gambaran Radiologis Kardiomegali pada Pasien Diabetes Mellitus Tipe 2 - Dinda Ananto Prameswari; Ricky Ramadhian (CV. Jasa Sukses Abadi, 2026)
Cardiomegaly is a condition characterized by enlargement of the heart that is often detected only after clinical symptoms develop. Type 2 diabetes mellitus is recognized as a major contributor to cardiovascular disease, including structural and functional cardiac abnormalities. This case report aims to describe the radiological findings of cardiomegaly in a patient with type 2 diabetes mellitus. A 44-year-old male presented with dyspnea that worsened during physical activity. Physical examination revealed a blood pressure of 176/88 mmHg, peripheral edema, and a cardiac murmur. Laboratory investigations showed hyperglycemia, normocytic normochromic anemia, and mild renal dysfunction. An anteroposterior (AP) chest radiograph demonstrated bilateral reticular opacities suggestive of interstitial pulmonary edema, widening of the right peritracheal stripe line suspicious for a vascular etiology, and cardiomegaly. Electrocardiography revealed evidence of left ventricular hypertrophy. The patient was diagnosed with type 2 diabetes mellitus, congestive heart failure (CHF), and normocytic normochromic anemia. Chronic hyperglycemia in diabetes mellitus may increase the production of reactive oxygen species (ROS), leading to oxidative stress, inflammation, myocardial hypertrophy, fibrosis, and cardiac remodeling, all of which contribute to the development of cardiomegaly and heart failure. Coexisting hypertension and chronic anemia may further aggravate these pathological processes. In this case, measurement of the cardiothoracic ratio (CTR) showed a value greater than 0.5, supporting the diagnosis of cardiomegaly. Chest radiography remains a useful initial screening modality for detecting cardiac enlargement in patients with type 2 diabetes mellitus.